The Role of Sambang by Bhabinkamtibmas in Empowering the Islamic Reform Movement (LINE) as a Form of Polmas Against Radical Groups in Cianjur Police - Herian, M. Iqbal Herian (Indonesian Journal of Police Studies, 2024)
Cianjur is an area with a Muslim majority population. In Cianjur, the spread of radical understanding was so rapid with the presence of several groups of organizations that were classified as radical. One of them is the GARIS mass organization, only at this time this mass organization is no longer classified as radical. This study aims to analyze and describe the efforts and factors that influence the implementation of sambang by bhabinkamtibmas. The research location in Polrest Cianjur with a focus on competing by bhabinkamtibmas in the empowerment of GARIS mass organizations. This study uses qualitative methods with descriptive analysis techniques. Using data triangulation (Moleong; 2006: 330) 4 (four) kinds of techniques, namely sources, theories and techniques as well as primary, secondary and tertiary data sources. Data validity is data reduction, data display, conclusion drawing and verification. This research uses Proactive Police Iceberg theory and Strategic Management theory as well as the concept of sambang, the concept of bhabinkamtibmas, the concept of community organizations, the concept of community policing and the concept of radicals. The implementation of the sambang by the bhabinkamtibmas which is not maximally carried out by the binmas unit is analyzed from the tentative symbol, the lack of human resources of the bhabinkamtibmas, which is not in accordance with the implementation of activities, geographical location, and use of official clothing. In implementing the symbol, there are influencing factors as discussed in the Environmental Scanning, Strategy Formulation, Strategy Implementation, and Evaluation and Control sections. The conclusion is that the inhibiting factors of the sambang by the bhabinkamtibmas are the spread of radical understanding in the Cianjur Regional Police Station which is still ongoing, the activity of the sambang is not optimal, and there are several factors that are not resolved.